Burnout and associated factors among nursing professionals at a municipal hospital (Research, Society and Development, 2021)
Aim: to describe the prevalence of suspicion and possible factors associated with burnout syndrome among critical care nursing professionals. Methodology: observational, descriptive, sectional epidemiological study. The population consisted of a sample of 85 nursing professionals from the intensive care sectors of a municipal public hospital. The translated and validated Portuguese version of the Maslach Burnout Inventory was used. Descriptive statistical analysis was performed with measures of central tendency, dispersion and frequency analysis. Data collection took place in January 2018. Results: the prevalence of suspected burnout syndrome was 40%, with 24.7% showing high emotional exhaustion, 18.8% high depersonification, and 08.2% low professional achievement. Having attended higher education (p = 0.028), a professional nurse (p = 0.009) and feeling stressed at work (p = 0.001), were associated with the syndrome. Conclusion: This syndrome can be triggered by different factors: work environment; organizational, personality, relationships. It is necessary to adopt preventive measures and control of diseases related to occupational stress.